Kudumbashree:Promoting the Self-Help Group Model of Empowerment Through Women Entrepreneurship in Kerala-A Study - Kumar, Ashutosh; C. J., Jasheena (Prabandhan: Indian Journal of Management, 2016)
Women are the basic unit of the society. They become even more important as a long-term solution to a sustainable livelihood. Women entrepreneurship through empowerment aims to create human resources within the productive sector and to sustain for the further development process. Kerala is only the state in India that has attained a remarkable status, fulfilling all the criterion of various social well-beings compared with some of the developed countries in the world, which is widely known as the 'Kerala model of development'. This achievement is reflected in the literacy level of women, salary or wage structure of employment, technical and professional services, equality of women at par with men. This political and socio-economic scenario within the state reinforces to redefine the consciousness about the poverty concept. In this sense, poverty is dynamically viewed as freedom of choice from a socioeconomic functioning than only the concern of income or money. Again, poverty reduction is not only a matter of an overall economic growth in a society, but also that is interconnected with various social aspects like women empowerment and women entrepreneurship. All these multi-dimensional approaches led the government to form a female community intended poverty reduction project in the state and resulted in the birth of "Kudumbashree". The mission has set up the self-help group (SHG) model of women empowerment to encourage a wide range of female entrepreneurial activities. Now, Kudumbashree has become one of the largest women's movements in Asia. This research study was conducted within the time period of three months from July to September 2015 among the female entrepreneurs those who are actively participating in the Kudumbashree mission in Kerala. The aim of this paper was to explore the activities and influence of Kudumbashree and the way it stimulates women empowerment as well as female entrepreneurship.